Perceptions of Teachers and Students Regarding the Middle School Honors Program - Selma Testa (Arizona State University, 2010)
This study examined the perceptions held by 40 teachers and 304 students of a middle school honors program. The sample population represented an equal number of honors and non-honors participants. Two surveys were analyzed using thematic coding for qualitative questions, while t test and descriptive statistics were used for quantitative results. The results confirm college and high school findings in the academic perceptions of the honors students, reasons for and against the enrollment, satisfaction with the program, and the over-representation of female and white students in the program, but reject specific identified characteristics of an honors student. Middle school honors students do not have the same qualities as high school and college honors students.